2015
DOI: 10.3389/fneur.2015.00228
|View full text |Cite
|
Sign up to set email alerts
|

The Virtual Brain: Modeling Biological Correlates of Recovery after Chronic Stroke

Abstract: There currently remains considerable variability in stroke survivor recovery. To address this, developing individualized treatment has become an important goal in stroke treatment. As a first step, it is necessary to determine brain dynamics associated with stroke and recovery. While recent methods have made strides in this direction, we still lack physiological biomarkers. The Virtual Brain (TVB) is a novel application for modeling brain dynamics that simulates an individual’s brain activity by integrating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 71 publications
(89 reference statements)
5
57
2
Order By: Relevance
“…In contrast to previous computational modeling studies that found increased global coupling values in chronic stroke patients (Falcon et al, 2015, 2016), our results revealed no significant differences in global coupling between glioma patients, meningioma patients, and healthy controls.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to previous computational modeling studies that found increased global coupling values in chronic stroke patients (Falcon et al, 2015, 2016), our results revealed no significant differences in global coupling between glioma patients, meningioma patients, and healthy controls.…”
Section: Discussioncontrasting
confidence: 99%
“…First, results showed a strong negative relation between global efficiency of the structural network and global coupling, corroborating the finding of Falcon et al (2015) in stroke patients. This implies that higher global coupling values are required in subjects whose structural connectome is less efficiently organized, to achieve the same amount of functional connectivity between cortical areas.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Our previous work using graph analysis [52] has shown that it is negatively correlated with global efficiency, or a network’s capacity for communication [18]. Because this still does not provide a clear biological interpretation, our current efforts are focusing on possible biophysical factors to provide better grounding to this parameter.…”
Section: The Virtual Brain-derived Models Are Sensitive To Disruptionmentioning
confidence: 99%